Controlling the Progression of Age-related Macular Degeneration Using the Image Quality Index and the Reference Image - Kowalski, Janusz P.; Peksinski, Jakub; Mikolajczak, Grzegorz (Elektronika ir Elektrotechnika, 2015)
This paper presented a possible application of a digital image quality measure, called the Universal Quality Image Index Q, for the diagnostics of the eye fundus. The proposed method supports examination of the progression of macular degeneration allowing to reduce the number of errors during a subjective examination by an ophthalmologist. This occurs mostly when changes are small between successive examinations. This paper proposes an effective algorithm to eliminate the errors during the subjective assessment caused by inaccurate synchronization of examined images. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13766